2019
DOI: 10.18698/2542-1468-2019-2-61-69
|View full text |Cite
|
Sign up to set email alerts
|

Variability of scotch pine linear increment in different types of biotopes in the European part of Russia

Abstract: Лесоведение Изменчивость линейного прироста сосны обыкновенной...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…So, it is shown that in Karelia, in the middle taiga region, an intensive linear growth of pine trees begins in the first half of May and reaches a maximum in mid-June, completely stopping in August (Kishchenko 2019). The amount of precipitation in this period can have both a positive (in case of insufficient moisture) and a negative (in case of excessive moisture) effect on the linear growth of Scots pine (Koukhta 2009;Volkova et al 2016;Pozdnyakova et al 2019). Previously, significant negative correlation between the precipitation in May-Jule and height growth indices of Scots pine growing here were found for humid biotopes of the northern regions (Pozdnyakova et al 2019).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…So, it is shown that in Karelia, in the middle taiga region, an intensive linear growth of pine trees begins in the first half of May and reaches a maximum in mid-June, completely stopping in August (Kishchenko 2019). The amount of precipitation in this period can have both a positive (in case of insufficient moisture) and a negative (in case of excessive moisture) effect on the linear growth of Scots pine (Koukhta 2009;Volkova et al 2016;Pozdnyakova et al 2019). Previously, significant negative correlation between the precipitation in May-Jule and height growth indices of Scots pine growing here were found for humid biotopes of the northern regions (Pozdnyakova et al 2019).…”
Section: Resultsmentioning
confidence: 55%
“…The amount of precipitation in this period can have both a positive (in case of insufficient moisture) and a negative (in case of excessive moisture) effect on the linear growth of Scots pine (Koukhta 2009;Volkova et al 2016;Pozdnyakova et al 2019). Previously, significant negative correlation between the precipitation in May-Jule and height growth indices of Scots pine growing here were found for humid biotopes of the northern regions (Pozdnyakova et al 2019). The same results (a negative correlation of the linear growth indices of Pinus sylvestris L. with the amount of precipitation in May and June) were obtained during examining the forest pine biotopes of the Baltic region with the cool humid Atlantic-Continental European climate (Janson et al 2013b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main types of pine response to various environmental conditions is its linear growth (=height growth). Its variability is closely related to climatic factors and ecological conditions (Koukhta 2003;Chernogaeva and Kuhta 2018;Jansons et al 2013a, b;Pozdnyakova et al 2019;Zhou et al 2019). The height growth of Pinus sylvestris L. in cold and moist regions is limited by the temperature in the previous summer and the length of the growing period (McCarroll et al 2003;Pensa et al 2005;Salminen and Jalkanen 2005).…”
Section: Introductionmentioning
confidence: 99%